Measuring the Design of Online Meeting Application Using Golden Ratio and Silver Ratio - Riska Wiradarma, Gede; Bharata Adji, Teguh; Fauziati, Silmi (International Journal of Engineering and Technology, 2018)
Several studies have attempted to create online meeting application, but the existing online meeting applications have not yet paid attention to User Interface and User Experience (UI and UX). To improve the UI and UX of online meeting applications, the existing design methods are implemented. The used methods are Golden Ratio and Silver Ratio. Those methods were tested empirically related to the effect of design methods on online meeting applications. The testing was done by collecting data in the field using User Experience Questionnaire (UEQ). The testing results of the UEQ showed that the attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty of the Golden Ratio Method appear to be better than the Silver Ratio Method. To ensure the correctness, the test was continued with testing the significance of UEQ data by using T-Test.Â